2013
DOI: 10.21123/bsj.10.3.934-944
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Salivary and Serum Proteins in Patients with Oral Tumors

Abstract: The qualified subjects for this study included 33 patients with benign and malignant oral tumors aged 15-75 years and 31 matched age and gender healthy subjects used as control. Proteins measurements included total protein, albumin, globulines in sera and saliva samples, and immunoglobulins (IgG, IgM, IgA) in sera samples of control and patients. Meanwhile, polyacrylamide gel electrophoresis (PAGE) was used to differentiate between protein patterns in both serum and saliva samples among the studied groups. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Comparing on the intergroup basis for the level of serum albumin, a statistically significant (p>0.05) value was found and our study result was in accordance with Singh et al Nayyar et al Chandran et al and Rajendran et al [12][13][14]17 While the rise in the level of serum globulin among OSMF cases can be attributed to the action of acute phase reactant and our study is in concordance with Dawood et al 18 Lipids are the major and essential components of a cell membrane that has different biological functions such as maintaining the functional and structural integrity of all biological membranes, as well as supporting in division and growth of the cell that may be a malignant or normal tissue. 19 Many studies have proved that various esophageal, as well as head and neck cancer, are directly associated with lowered blood lipid levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparing on the intergroup basis for the level of serum albumin, a statistically significant (p>0.05) value was found and our study result was in accordance with Singh et al Nayyar et al Chandran et al and Rajendran et al [12][13][14]17 While the rise in the level of serum globulin among OSMF cases can be attributed to the action of acute phase reactant and our study is in concordance with Dawood et al 18 Lipids are the major and essential components of a cell membrane that has different biological functions such as maintaining the functional and structural integrity of all biological membranes, as well as supporting in division and growth of the cell that may be a malignant or normal tissue. 19 Many studies have proved that various esophageal, as well as head and neck cancer, are directly associated with lowered blood lipid levels.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were observed by Patidar et al, Rajendran et al, and Dawood et al among cases and controls, whereas Chandran et al study findings differ from our result. 13,[16][17][18] In oral malignancy, the rise in the level of serum protein levels may be due to inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Metgud and Patel reported that oral leukoplakia and oral cancer patients are associated with low albumin levels in comparison with healthy subjects. According to various studies, serum albumin has a vital role in the early identification of oral premalignant lesions and conditions [ 29 - 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chewing tobacco users with oral submucous fibrosis had lower serum albumin levels than controls ( Ahmad et al, 2022 ). In oral cancer patients, serum albumin levels are lower and salivary albumin levels are higher than those in healthy controls ( Dawood and Hasan, 2013 ). Serum albumin levels and clinical attachment loss, a marker of periodontitis, are associated with head and neck cancer ( Maruyama et al, 2012 ).…”
Section: Serum and Salivary Albumin Tests In Recent Oral Health-relat...mentioning
confidence: 99%
“… Case-control Serum albumin level OSF Serum albumin Serum albumin was significantly reduced in patients with chewing tobacco habit with OSF compared to the control group. Yes ( Dawood and Hasan, 2013 ) 33 patients with oral tumors aged 15–75 compared with healthy controls. Case-control Serum and salivary albumin Oral tumors Serum and salivary albumin Compared to the control group, patients' serum albumin decreased and salivary albumin increased significantly.…”
Section: Serum and Salivary Albumin Tests In Recent Oral Health-relat...mentioning
confidence: 99%